Global excellence in rheumatology in Latin America: The case of systemic lupus erythematosus - Ugarte-Gil, Manuel F.; Fuentes-Silva, Yurilis; Pimentel-Quiroz, Victor R.; Pons-Estel, Guillermo J.; Quintana, Rosana; Pons-Estel, Bernardo A.; Alarcón, Graciela S. (Frontiers in Medicine, 2023)
Systemic lupus erythematosus (SLE) affects more severely non-White populations, due to their genetic background and sociodemographic characteristics. Several studies have evaluated Latin American SLE patients to determine their genetic and clinical characteristics as well as prognostic factors; these studies have not only allowed the development of treatment guidelines aimed at the region but also to support regional and global projects. Additionally, educational activities in Spanish and Portuguese have been started to reduce our patients’ health illiteracy. Despite the relatively low research output from Latin American countries, we consider that studies from our region coupled with the networks developed to increase our capabilities, could be a model for other rare autoimmune diseases.